Response of potato to nitrogen and potassium in alluvial soil of South-Western plain zone of Uttar Pradesh - Ali, Javed; Singh, S.P. (Annals of Agricultural Research, 2014)
Field experiments were conducted at Bichpuri during rabi seasons of 2009-10 and 2010-11 to study the effect of nitrogen (N) and potassium (K) levels on yield and nutrient uptake of potato. Sixteen treatment combinations consisted of four levels each of (0, 100, 200 and 300 kg/ha)and K (0, 60, 120 and 180 kg K2O/ha, replicated thrice, were arranged in randomized block design. The tuber yield was significantly increased by both the nutrients over control. The highest tuber yield (30.54 t/ha), recorded with the highest levels of N and K, was nearly double the yield recorded under control (11.77 t/ha). Similar trend was observed for dry matter yield. The uptake of N, P, K and S significantly increased with increase in N and K application rate. The interaction effect between N and K significantly and synergistically influenced the tuber and dry matter yields, which were observed the highest at 300 kg N in conjunction with 180 kg K2O/ha.